ASPECTS OF THE HARMONY OF CULTIC CHOIRS FROM OEDIPUS BY GEORGE ENESCU - Petruţa-Maria COROIU (MĂNIUŢ) (Studia Universitatis Babeş-Bolyai. Musica)
The last three concerts composed by Aurel Stroe are a further proof of his compositional maturity. The third concert proposes the ideal model of the “chord-matrices”, a symbol that we have to reveal in the spiritual dimensions of Aurel Stroe’s music.